STRATEGI PENERAPAN KONSEP PESERTA DIDIK YANG IDEAL MENURUT IMAM AZ-ZARNUJI DALAM KITAB TA'LIMUL MUTA'ALLIM DI MAHAD ALY PONDOK PESANTREN AL-ISHLAHUDDINY KEDIRI LOMBOK BARAT - Hamdani Hamdani; Abdul Fattah; Salimul Jihad (Universitas Islam Negeri Mataram, Indonesia, 2019)
The Book of Ta‘limul Muta‘allim is one of a series of yellow books which are widely studied and become guidelines for santri in Islamic boarding schools. Al-Ishlahuddiny Islamic Boarding School Kediri Lobar is one of the huts that studies the book Ta'limul Muta'allim, and the book in the al-Ishlahuddiny boarding school is used as a reference to form students who become moral children, this cottage is not it sounds strange because this cottage is one of the oldest cottages in Lombok. This cottage, when viewed from the output side, has printed many polite students, tawaddu ', waro', preachers, experts in yellow books and become ustaz ustazah and master teachers. At the alIshlahuddiny Islamic boarding school in the Mahad Aly section of the institution, the contents of the book Ta‘limul Muta‘allim have been applied as a reference to form students who become moral students. The purpose of this study is to explain the strategy of applying the ideal concept of students according to imam az-Zarnuji in the book Ta'limul Muta’allim in Mahad Aly pondok pondokren al-Ishlahuddiny kediri Lombok Barat and the results of its application in the Pondok. The type of research used in this study is qualitative research that uses a phenomenological approach. For data collection used in this study are observation, interviews, and documentation. Based on the results of this study through observation, interviews, and documentation about the strategy of applying the ideal concept of students according to imam az-Zarnuji in the book Ta'limul Muta'allim in Mahad Aly Islamic boarding school al-Ishlahuddiny Kediri Lombok Barat using several strategies namely the attitude of exemplary, habituation, devotion, and giving advice. While the results of the implementation strategy are Mahad Aly students of Al-Ishlahuddiny Islamic Boarding School to be respectful to teachers and knowledge, waro ', patience and resignation and discipline.